Analysis of extreme ultraviolet spectra from laser produced rhenium plasmas. (10th July 2015) - Wu, Tao; Higashiguchi, Takeshi; Li, Bowen; Suzuki, Yuhei; Arai, Goki; Dinh, Thanh-Hung; Dunne, Padraig; O'Reilly, Fergal; Sokell, Emma; Liu, Luning; O'Sullivan, Gerry
Abstract: Extreme ultraviolet spectra of highly-charged rhenium ions were observed in the 1–7 nm region using two Nd:YAG lasers with pulse lengths of 150 ps and 10 ns, respectively, operating at a number of laser power densities. The maximum focused peak power density was 2.6 × 10 14 W cm −2 for the former and 5.5 × 10 12 W cm −2 for the latter. The Cowan suite of atomic structure codes and unresolved transition array (UTA) approach were used to calculate and interpret the emission properties of the different spectra obtained. The results show that n  = 4- n  = 4 and n  = 4- n  = 5 UTAs lead to two intense quasi-continuous emission bands in the 4.3–6.3 nm and 1.5–4.3 nm spectral regions. As a result of the different ion stage distributions in the plasmas induced by ps and ns laser irradiation the 1.5–4.3 nm UTA peak moves to shorter wavelength in the ps laser produced plasma spectra. For the ns spectrum, the most populated ion stage during the lifetime of this plasma that could be identified from the n  = 4- n  = 5 transitions was Re 23+ while for the ps plasma the presence of significantly higher stages was demonstrated. For the n  = 4- n  = 4 4p 6 4d N -4p 5 4d N+1  + 4p 6 4d N−1 4f transitions, the 4d-4f transitions contribute mainly in the most intense 4.7–5.5 nm region while the 4p-4d subgroup gives rise to a weaker feature in the 4.3–4.7 nm region. A number of previously unidentified spectral features produced by n  = 4- n  = 5 transitions in the spectra of Re XVI to Re XXXIX are identified.